Dogmatic Analysis of the Tension Between the Rights of Nature and Large-Scale Mining, Within the Framework of the Ecuadorian Constitution. - Carla Grefa Valencia; William Sacher Freslon (Ius Humani. Jornal do direito, 2023)
With the 2008 Constitution, Ecuador became a pioneer in the constitutional recognition of nature as a legal subject, while at the same time promoting large-scale mining and placing it at the center of its economic future. Against this backdrop, the article focuses on the analysis of possible dogmatic contradictions within the Ecuadorian legal framework, between the rights of nature and mining rights related to large-scale mining operations. In this sense, a synthesis of the trajectory and development of the rights of nature in Ecuador is presented, as well as the historical passage of large-scale mining in the country and a brief synthesis of the environmental impacts documented in the academic literature. Based on this, a series of points of dogmatic tension were identified, according to the terms of the Ecuadorian Constitution. For the development of this article, the theoretical-doctrinal method was used, through two levels: hermeneutic and theoretical-dogmatic. It is argued that the Ecuadorian legal regime has not been constructed or updated to integrate the premises of the constitutional recognition of the rights of nature nor the potential violations of these rights caused by large-scale mining activities.